OPTIMASI PEMANFAATAN ABU SEKAM PADI SEBAGAI FILLER RAMAH LINGKUNGAN PADA CAMPURAN AC-WC - Faqih, Hasan Nur; Novriani, Shinta (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
The use of agricultural waste as a construction material is a strategic approach to strengthen the concept of sustainable construction. Rice husk ash is a potential product through the process of burning rice husks. This material can be an alternative as a filler in the AC-WC mixture layer. This study aims to optimize the use of rice husk ash as an environmentally friendly filler. This study uses a quantitative approach based on laboratory results starting from testing material gradation, mud content, SPGR, and GMM. Then Marshall briquettes were made with various filler levels, then Marshall tests were carried out to determine the stability, flow, density, VIM, VMA, and VFB values. The results showed that the characteristics of the mixture were influenced by the addition of rice husk ash. The stability value at 2% content was obtained at 1271.4 kg, with a flow value of 2.96 mm and a density of 2.267 gr/cm³. The VIM, VMA, and VFB values of 3.85%, 18.26%, and 78.95%, respectively, still meet the required specifications. The use of 2% not only produces optimal mixture performance but also provides a more valuable and sustainable use of agricultural waste. Keyword: Rice Husk Ash, AC-WC, Environmentally Friendly, Marshall Test.